O atentado de 11 de setembro de 2001 em dois momentos na televisão: uma reportagem factual e outra de infotenimento - Tramontina, Tatiana (2020)
The present study analyzes the use of infotainment in reports produced by journalist Jorge Pontual, for Rede Globo’s programs Fantástico e Globo Repórter, in the face of the terrorist attacks of September 11, 2001. To understand the term television reporting and television travel report, it was used as basis Jespers (1998), Neves (2007) and Hannerz (2004). The methodology, supported by the idea of infotainment, has Gomes (2009) as a reference, pointing out the sense of hybridization between information and entertainment. It was possible to analyze the presence of infotainment characteristics in the two reports, although one of them was produced with a more factual character.